PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT INDOWARNA NUSANTARA TANGERANG SELATAN - Dwi Marcella, Shafira; Rizka Akbar, Irfan (Journal of Research and Publication Innovation, 2024)
This research aims to determine the influence of motivation and work discipline on employee performance at PT. Indowarna Nusantara South Tangerang either partially or simultaneously. The research method used is quantitative and associative in nature. The sampling technique totaling 60 employees. Data collection techniques through primary and secondary data. The results of the research show that motivation (X1) and work discipline (X2) influence employee performance (Y) with a regression equation of Y = 13,215 + 0,293 (X1) + 0,354 (X2) with a coefficient of determination of 33,9%. Partial hypothesis test results influence motivation. On employee performance with the results of the t test > t table or 3,449 > 2,002, then 〖Ho〗_1 is rejected and 〖Ha〗_1 is accepted. Partially, work discipline influences employee performance with results of the t test > t table or 4,502 > 2,002, so 〖Ho〗_2 is rejected and 〖Ha〗_2 is accepted. The results of simultaneous hypothesis testing are calculated F Value > F table or 14,623 > 3,16, so 〖Ho〗_3 is rejected and 〖Ha〗_3 is accepted. It can be concluded that the research results show that motivation and work discipline influence employee performance at PT. Indowarna Nusantara South Tangerang.